The importance of financial data consolidation in the context of open finance for product and service innovation/A importancia da consolidacao dos dados financeiros no contexto do open finance para a inovacao de produtos e services/La importancia de la consolidacion de datos financieros en el contexto de las finanzas abiertas para la innovacion de productos y servicios - Ramos, Rommel Gabriel Goncalves; Proenca, Nayara Reis Barbosa; Nunes, Thales Oliveira; de Souza, Anderson Ferreira; Rocha, Anderson Jacob; Lemos, Estefania Portomeo Cancado; da Silva, Hugo Marques; dos Santos, Erick Quintino (GeSec : Revista de Gestão e Secretariado, 2024)
Today, a digital revolution is taking place. People live in a constant search for digital solutions that solve their problems quickly and practically. In the midst of this revolution, the Central Bank has implemented Open Banking Brazil, now called Open Finance, thus facilitating the sharing of people's financial data between financial institutions. With this new way of working, difficulties and major technological innovations arise. Thus, in view of the importance and timeliness of the subject, it is necessary to study the topic Open Banking Brazil. Open Banking is being implemented in Brazil to promote innovation, standardization of financial institutions systems, and data sharing in order to foster competitiveness and enable the supply and delivery of a better product/service better suited to consumer needs. Some of the advantages of this system are: greater competitiveness, access to lower rates and better conditions, the guarantee of security and privacy, ease and practice for sharing and payments, and the free service. However, there are problems of inconsistency in the communication of systems between participating financial institutions. It turned out that the program is going to bring grandiose technological development to the financial area, as well as to all Information Technology. Yes, major projects in the area of Artificial Intelligence and Machine Learning are already being returned to the financial institutions. Keywords: Open Banking Brazil. Open Finance Brazil. API. Technology. Innovation. Consolidation. Finance. Atualmente, esta acontecendo uma revolucao digital. As pessoas vivem em uma busca constante por solucoes digitais que resolvam seus problemas de forma rapida e pratica. Em meio a essa revolucao, o Banco Central tem implementado o Open Banking Brasil, agora chamado Open Finance, facilitando assim o compartilhamento de dados financeiros de pessoas, entre instituicoes financeiras. Com essa nova forma de trabalhar, surgem dificuldades e grandes inovacoes tecnologicas. Assim, diante da importancia e atualidade do assunto, fazse necessario um estudo sobre o tema Open Banking Brasil. O Open Banking, esta sendo implementado no Brasil para promover a inovacao, a padronizacao dos sistemas das instituicoes financeiras, e o compartilhamento dos dados, a fim de fomentar a competitividade e possibilitar a oferta e a entrega de um produto/servico melhor e mais adequado as necessidades do consumidor. Algumas das vantagens desse sistema sao: a maior competitividade, o acesso a tarifas mais baixas e melhores condicoes, a garantia da seguranca e privacidade, a facilidade e pratica para compartilhamento e pagamentos, e a gratuidade do servico. Contudo, existem problemas de inconsistencia na comunicacao dos sistemas entre as instituicoes financeiras participantes. Verificou-se que o programa vai trazer um desenvolvimento tecnologico grandioso para area financeira, bem como para toda a Tecnologia da Informacao. Pois, ja estao sendo devolvidos grandes projetos na area de Inteligencia Artificial e Machine Learning, para as instituicoes financeiras. Palavras-chave: Open Banking Brasil. Open Finance Brasil. API. Tecnologia. Inovacao. Consolidacao. Financas. Hoy en dia, se esta produciendo una revolucion digital. La gente vive en una busqueda constante de soluciones digitales que resuelvan sus problemas de forma rapida y practica. En medio de esta revolucion, el Banco Central implemento Open Banking Brazil, ahora llamada Open Finance, facilitando asi el intercambio de datos financieros de la gente entre instituciones financieras. Con esta nueva forma de trabajar, surgen dificultades y grandes innovaciones tecnologicas. Por lo tanto, en vista de la importancia y oportunidad del tema, es necesario estudiar el tema Open Banking Brazil. En el Brasil se esta aplicando la banca abierta para promover la innovacion, la normalizacion de los sistemas de instituciones financieras y el intercambio de datos a fin de fomentar la competitividad y permitir el suministro y la prestacion de un producto o servicio mejor adaptado a las necesidades de los consumidores. Algunas de las ventajas de este sistema son: mayor competitividad, acceso a tarifas mas bajas y mejores condiciones, la garantia de seguridad y privacidad, facilidad y practica para compartir y pagar, y el servicio gratuito. Sin embargo, existen problemas de incoherencia en la comunicacion de los sistemas entre las instituciones financieras participantes. Resulto que el programa traera un desarrollo tecnologico grandioso al area financiera, asi como a toda la Tecnologia de la Informacion. Si, los grandes proyectos en el area de Inteligencia Artificial y Aprendizaje Automatico ya estan siendo devueltos a las instituciones financieras. Palabras clave: Banca Abierta Brasil. Open Finance Brasil. API. Tecnologia. Innovacion. Consolidacion. Finanzas.